Sistem Informasi Promosi Tempat Wisata Di Kota Sorong Berbasis Website (Kasus: Kawasan Wisata Mangrove Klawalu) - Manuhutu, Melda Agnes; Otniel, O (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2021)
The Klawalu Mangrove Tourism Area is a mangrove forest tourist spot managed by the Sorong City Tourism Office, located in Klawalu Village, Sorong City. The research aims to build an attractive website to facilitate the Sorong City Tourism Office in promoting the Klawalu Mangrove Tourism Area. Thus the public can more easily access information, which can directly increase public interest from inside and outside the City of Sorong. The more tourists who visit, it will increase economic growth in the City of Sorong Region. By increasing the productivity of the tourism sector, it is hoped that it will be able to provide fast economic growth in terms of employment opportunities, income, living standards and in activating the production sector. The system development method is the prototype method. The programming language used is PHP with a database built using MySQL. The modeling language used is the Unified Modeling Language (UML). With the advantages of a more responsive template, there is google maps, and provides information about facilities and entrance fees for tourist attractions.